(untitled) (Asian Journal of Medical Sciences, 2024)
Cranioplasty, the surgical restoration of cranial defects, has been a crucial procedure in neurosurgery for decades. Titanium mesh has emerged as a popular choice for cranial reconstruction due to biocompatibility and ability to confirm the patient’s unique cranial contours. While generally considered safe, titanium mesh cranioplasty is not without complications. This case report presents a challenging and atypical scenario of a patient who developed flap necrosis following titanium mesh cranioplasty. We aim to highlight the complexity of managing such cases and the importance of timely diagnosis and intervention.